Cerebrovascular Operative Anatomy: An Immersive 3D and Virtual Reality Description. Issue 6 (15th November 2018) - Hendricks, Benjamin K; Hartman, Jerome; Cohen-Gadol, Aaron A
Abstract: BACKGROUND: The innate detail of the cerebrovasculature is a demonstration of the structural complexity exhibited within the nervous system and highlights the challenges intrinsic to surgically influencing this system. Bridging the knowledge gap between the 2-dimentional learning environment and the 3-dimensional (3D) clinical setting is a challenge requiring experience. Computer graphic technology provides an opportunity for the learner to step into a new era of learning via the use of interactive 3D models and virtual reality. OBJECTIVE: To create virtually anatomically accurate cerebrovascular models with superior detail and visual appeal. METHODS: High-resolution angiographic radiological studies were utilized to create virtual 3D models which were edited for anatomical accuracy and artistry post-processing. RESULTS: We have created anatomically realistic and detailed 3D virtual models of the cerebrovascular structures including the arterial and venous systems. The relevant surgical anatomy of the bony and brain structures was also included. In addition, these models were used to illustrate the pathoanatomy of a deep vascular malformation to demonstrate the potential of this technology. These models allow user interactivity in the 3D environment for improved understanding of anatomical relationships. CONCLUSION: Advances in computer graphics have invited a new era of education and experiential learning. The authors have created an immersive virtual 3D model of the cerebrovasculature to augment education, research, and clinical applications.